EFEKTIVITAS PENGGUNAAN KEKUATAN OLEH KEPOLISIAN DALAM MENANGANI AKSI UNJUK RASA ANARKIS DI KOTA PADANG (Studi Pada Satsabhara Polresta Padang) - Saputra, Sigit; Rosadi, Otong (LPPM Universitas Ekasakti Padang, 2019)
Broadly speaking, gather and issue opinions as stipulated in Article 28 (e) Paragraph (3) of the 1945 Constitution, independence expresses opinion as stipulated in Law No. 9 of 1998, then everyone has the right to freedom of association. The practice is in the field, many demonstrations taste or demonstration that ended in riots that led to anarchists. In carrying out the task of handling mass riots during the Police demonstration using 1) Perkap No. 16 of 2006 concerning Mass Control Guidelines, 2) Protap/1/X/2010 concerning Countermeasures for Anarchy, 3) Perkap No. 1 of 2012 concerning Mass Unraveling Platoon, 4 ) Perkap No. 7 of 2012 concerning Procedures for Organizing Services, Safeguards and Handling of Cases of Public Opinion. The problems in this thesis are: First, how is the use of force by the Padang Police Satsabhara in dealing with anarchist demonstrations in Padang City? Second, the obstacles encountered by Padang Satsabhara in handling anarchist demonstrations in Padang City and how to overcome these obstacles? Third, how effective is the use of force by the Padang Police Satsabhara in handling anarchist demonstrations in Padang City?The specification of this research is a descriptive analytical study. The approach used is normative juridical as the main approach and supported by an empirical juridical approach. The data used is secondary data and primary data. The data obtained were analyzed qualitatively and presented descriptively analytically. Based on the research and discussion, it can be seen that: First, the use of force by Satsabhara Polresta Padang in handling anarchist demonstrations in Padang City includes organizing services, organizing security and handling cases, carried out by using force, such as in the preparation stage before the demonstration , in the event of anarchist demonstrations and at the time of anarchist demonstration activities are over. Second, the obstacles encountered by Padang Satsabhara Polresta in handling anarchist demonstrations in Padang City are human rights problems, provocation from certain parties, legal unconsciousness of the community and lack of coordination with the Police and related agencies. Whereas the efforts made in handling the demonstration are; a). pre-emptive effort, b). preventive efforts, c). repressive efforts. Then the Police also made several efforts, namely by increasing the professionalism of members of the Police, coordinating with relevant agencies and conducting legal counseling to the community. Third, the effectiveness of the use of force by the Padang Police Satsabhara in handling anarchist demonstrations in Padang City based on its duties and authorities has shown performance in police actions to deal with anarchic demonstrations in Padang City that are optimal with the number of anarchist rallies in Padang City that have been handled.